1997
DOI: 10.1007/bf01708235
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hydrogen peroxide-producing strains of lactobacilli and vaginosis-associated bacterial species in pregnant women

Abstract: This study was conducted to determine the relationship between lactobacilli and bacterial species associated with bacterial vaginosis in pregnancy and the prevalence of H2O2-producing and non-producing strains of lactobacilli in pregnant women whose vaginal flora had already been analysed. Information was available for 174 pregnant women whose vaginal flora had been evaluated previously by examining gram-stained vaginal smears: 50 had grade III flora (bacterial vaginosis). 50 grade II flora, 41 flora graded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…Upon exposure to air, colonies producing H 2 O 2 appeared blue. The time taken for the appearance of the blue colouration was recorded and used as an indication of the quantity of H 2 O 2 produced [17].…”
Section: H 2 O 2 Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon exposure to air, colonies producing H 2 O 2 appeared blue. The time taken for the appearance of the blue colouration was recorded and used as an indication of the quantity of H 2 O 2 produced [17].…”
Section: H 2 O 2 Productionmentioning
confidence: 99%
“…H 2 O 2 -producing strains, which are thought to be inhibitory to other bacterial species, have been found signi®cantly more frequently in women with a normal vaginal¯ora than in women with BV [16]. However, the proportion of H 2 O 2 -producing strains isolated from pregnant women with BV may be higher [17].…”
Section: Introductionmentioning
confidence: 99%
“…8 Histology was carried out by a single observer (LP) blinded both to the gel used and to whether the specimen was taken before or after exposure. Where evidence of an inflammatory infiltrate was seen, specimens were further assessed using the immunohistological technique previously described.…”
Section: Histologymentioning
confidence: 99%
“…8 High vaginal swabs taken at each visit were cultured for a quantitative estimation of vaginal lactobacilli as described previously. 8 Vaginal flora were sampled at 12 hours after the last gel dose during the exposure phase of the study in the UK cohort whereas in the Belgian cohort, sampling was carried out 2 hours after gel insertion.…”
Section: Microbiologymentioning
confidence: 99%
“…The growing presence of Lactobacilli during pregnancy allows maintaining a low pH in the vaginal environment, thus limiting bacterial diversity, reducing the incidence of bacterial vaginosis 12 and preventing the pathogens rise to the uterus, where they may infect amniotic fluid, placenta and foetus. 13,14 Animal studies have shown that changes in the maternal gut microbiota can promote the growth of the mice.…”
Section: Maternal Microbiota During Pregnancymentioning
confidence: 99%